2019
DOI: 10.1002/adsc.201900109
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Cascade Synthesis of (3S)‐Hydroxyketones Catalyzed by Transketolase via Hydroxypyruvate Generated in Situ from d‐Serine by d‐Amino Acid Oxidase

Abstract: We described an efficient in situ generation of hydroxypyruvate from d-serine catalyzed by a damino acid oxidase from Rhodotorula gracilis. This strategy revealed an interesting alternative to the conventional chemical synthesis of hydroxypyruvate starting from toxic bromopyruvate or to the enzymatic transamination from l-serine requiring an additional substrate as amino acceptor. Hydroxypyruvate thus produced was used as donor substrate of transketolases from Escherichia coli or from Geobacillus stearothermop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 50 publications
1
7
0
1
Order By: Relevance
“…Next, we investigated whether both enzymes would also be able to perform decarboxylating carboligations with oxalyl‐CoA as C 1 ‐donor. We argued that the release of CO 2 should provide a strong thermodynamic driving force towards carboligation, analogous to the reactions reported for glyoxylate carboligase, PDC, BFD, TK, and KdcA . HACL Hs possessed only very low oxalyl‐CoA decarboxylation activity ( k cat <1 min −1 , see Figure S2 in the Supporting Information), in contrast to OXC Me ( k cat =98±3 s −1 , see Table and Figure S3 in the Supporting Information), which confirms OXC Me ’s physiological function as oxalyl‐CoA decarboxylase.…”
Section: Methodssupporting
confidence: 76%
“…Next, we investigated whether both enzymes would also be able to perform decarboxylating carboligations with oxalyl‐CoA as C 1 ‐donor. We argued that the release of CO 2 should provide a strong thermodynamic driving force towards carboligation, analogous to the reactions reported for glyoxylate carboligase, PDC, BFD, TK, and KdcA . HACL Hs possessed only very low oxalyl‐CoA decarboxylation activity ( k cat <1 min −1 , see Figure S2 in the Supporting Information), in contrast to OXC Me ( k cat =98±3 s −1 , see Table and Figure S3 in the Supporting Information), which confirms OXC Me ’s physiological function as oxalyl‐CoA decarboxylase.…”
Section: Methodssupporting
confidence: 76%
“…The reaction catalyzed by DTA cell-free extract was studied using substrate concentrations of 50 and 100 mM (Table ). Lower concentrations were not chosen because we previously showed that the best result for the d -serine conversion catalyzed by DAAO Rg was obtained at 50 mM …”
Section: Resultsmentioning
confidence: 99%
“…Lower concentrations were not chosen because we previously showed that the best result for the D-serine conversion catalyzed by DAAO Rg was obtained at 50 mM. 15 A concentration of 50 mM for both substrates was used to perform the reaction because almost complete substrate conversion of both substrates (94%) was obtained after 24 h, against 82% with both substrates at 100 mM. The reaction mixture was treated with methanol to precipitate proteins and to avoid byproduct formation from substrates and reagents used in steps 2 and 3.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Als nächstes untersuchten wir, ob beide Enzyme auch decarboxylierende Carboligationsreaktionen mit Oxalyl‐CoA als C 1 ‐Donor katalysieren können. Die Freisetzung von CO 2 erzeugt eine starke thermodynamische Triebkraft in Richtung Carboligation, analog zu den Reaktionen von Glyoxylat‐Carboligase, PDC, BFD, TK und KdcA . HACL Hs zeigte eine sehr geringe Oxalyl‐CoA‐Decarboxylierungsaktivität ( k cat <1 min −1 , siehe Abbildung S2), im Gegensatz zu OXC Me ( k cat =98±3 s −1 , siehe Tabelle und Abbildung S3), was die physiologische Funktion von OXC Me als Oxalyl‐CoA Decarboxylase bestätigt.…”
Section: Methodsunclassified